PENUMBUHAN DAN KARAKTERISASI NANOPARTIKEL PERAK PADA SUBSTRAT PADAT - Rizky Ardie Yani; Iwantono '; Akrajas Ali Umar (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Silver nanoparticles have been successfully grown on solid substrate. The growth of the particles used wet chemical method which consisted of two steps, seeding and growing steps. The silver nanoparticle growth was carried out by two variations which were surfactant’s concentration and ascorbic acid’s volume. The UV-Vis spectrum profile of the samples described that the growth of silver nanoparticles of spherical shape was dominated on the ITO, represented as a sharp single peak of the absorption spectra. Its characterization measured by XRD showed that silver nanoparticles had grown on the substrate with crystal orientation (1 1 1) and (2 0 0). The FESEM images depicted that the shape of silver nanoparticles was a spherical shape with their uniform diameter size of 300-650 nm.